STRENGTHENING STUDENTS' RELIGIOUS CHARACTER THROUGH THE TAHFIDZ QUR'AN PROGRAMME OF THE JUZ 30 MEMORISATION COMMUNITY AT STATE PRIMARY SCHOOL 21 TOLOMUNDU - Ramadhan, Syahru; Hakiki, Ainun; Miratunnisa, Ainun; Nenoningsih, Nur; Darti, Darti; Fadilah, Aan (Waniambey: Journal of Islamic Education, 2024)
The Tahfidz Al-Qur'an programme is one of the answers to various problems about the lack of cultivation of children's religious character in the face of an increasingly developing digital world and followed by the existence of outside cultures that enter the scope of children's lives. By looking at the number of crime rates, acts of discrimination, and attitudes of disrespect or intolerance with others, so that in the scope of especially elementary schools it is very necessary to make efforts to strengthen the character of students, especially the value of religiosity. In this study, researchers collected information, studied, and analysed in a qualitative descriptive form. Data sources in this study were collected using observation, interview and documentation techniques. Data analysis was conducted based on the facts that occurred during the research which were described in a structured manner. The results of this study indicate that strengthening the religious character of students can be implemented using the tahfdz Al- qur'an programme and has a positive impact on the development of student competence both in the aspects of knowledge, attitudes, and skills.